How Campaigns Enhance European Issues Voting During European Parliament Elections. Issue 4 (27th March 2017) - Beach, Derek; Hansen, Kasper M.; Larsen, Martin V.
Abstract : Based on findings from the literature on campaign effects on the one hand, and the literature on European Parliament elections on the other, we propose a model of European Parliamentary elections in which the campaign shift the calculus of electoral support, making differences in national political allegiances less important and attitudes about the European project more important by informing voters of and getting them interested in European politics. In effect, we argue that the political campaign leading up to the election makes European Parliament elections less second order. While previous studies have demonstrated that EU issues can matter for voting behavior in European Parliament elections, existing research has drawn on post-election surveys that do not enable us to capture campaign effects. Our contribution is to assess the impact of a campaign by utilizing a rolling cross-sectional survey that enables us to track how voters were affected by the campaign. Our findings show that campaigns do have an effect on European Parliament election outcomes, in that they provide information that enables voters to make decisions based on their attitude on European issues, making voter decision-making more dominated by EU issue voting.